Principals’ experiences of legal processes affecting post- primary schools, with particular reference to Section 29 of the Education Act, 1998. - Duffy, Ciarán (Trinity College (Dublin, Ireland). School of Education, 2022)
The purpose of this dissertation is to determine the influence of the law on the Leadership and Management of post-primary schools in Ireland and associated legal processes. The dissertation rationale arose from a literature review of legislation and caselaw from the courts in Ireland. The methodology employed a purposive sampling of post-primary school principals involved in the appeal mechanism of the DE as established under Section 29 of the Education Act, 1998 and recently updated in line with the Education (Admission to Schools) Act 2018. The research findings indicate that principals very often don’t view their role as legal in nature but take due care to follow circulars, guidance and legislation. These principals have a positive outlook on the law through their interactions with lawyers from whom they seek legal advice. The law is essential to ensure publicly funded schools are accountable for their actions or neglect of their actions. Lawyers representing insurance companies play a significant role in settling claims outside of court and in bringing vexatious claims to a judge to be arbiter of the facts of the case. It is a strong recommendation to press upon principals and Boards of management to have all of their school policies proofread by lawyers. Certain school policies and practices may indeed be illegal. It is advisable for principals to be aware of case law which may bring about changes to legislation. Legislation will allow for a degree of discretion for school policies but will not allow for any discriminatory practices. It is ever so important that the universal principles of constitutional and natural justice; are provided for the whole school community.
Keywords: Leadership and Management; Education